Altrenogest and fat for summer breeding of first-litter sows - Jeffrey S Stevenson; Duane L Davis; D S Pollmann (Kansas Agricultural Experiment Station Research Reports, 1984)
Crossbred first-Iitter sows in a commercial swine unit were assigned to serve as controls after summer weanings or were fed altrenogest for 7 days or altrenogest for 7 days plus supplemental fat for 14 days after weaning. While similar proportions of sows came into heat after weaning, sows fed altrenogest returned to estrus about 9 days later than control sows. Incidence of anestrus was similar across sow groups (31%), while most of the sows not detected in heat could be classified by cause after examining serum progesterone concentrations at 3 wk after weaning. Nearly 69 % of the sows not detected in heat had luteal function, indicating a failure to detect sows when in true estrus or failure of sows to show behavioral estrus. Farrowing traits were similar among treatments, however, there was a tendency for sows fed altrenogest to have higher farrowing rates.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Swine; Altrenogest; Fat; First-litter sows